Fitting Structural Equations Models with Interactive and Dynamic Tools in JMP® Pro. Issue 5 (3rd September 2021) - Castro-Schilo, Laura; Russo, Eric
ABSTRACT: We offer a tutorial for using a new, interactive, and dynamic Structural Equation Modeling (SEM) platform in JMP Pro v16.0 to fit three commonly used models: (1) Confirmatory Factor Analysis, (2) Path Analysis with Latent Variables, and (3) Longitudinal Factorial Invariance Analysis. We highlight features of JMP Pro through these examples including, an end-to-end workflow that enables all stages of data manipulation, visualization, analysis, and presentation, the dynamic feedback provided in the SEM specification process to guard against errors, interactive customizations of path diagrams and model comparison tools, novel visualizations for assessing reliability and validity of measurement models, and sharing capabilities for enabling collaborations.